1991
DOI: 10.1128/iai.59.10.3523-3530.1991
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose-promoted accumulation of growing glucosyltransferase variants of Streptococcus gordonii on hydroxyapatite surfaces

Abstract: Streptococcus gordonui exhibits a phase variation involving expression of high (Spp+) or low (Spp-) glucosyltransferase activity. The related bacterial accumulation on hydroxyapatite (HA) and saliva-coated HA surfaces was examined and found to be significant. Spp+ cells growing anaerobically in a defined medium utilize about 30% of the glucose available from sucrose to make insoluble glucans. These glucans formed cohesive masses on HA beads, which contained 80 to 90% of the total bacteria. The bacterial polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 31 publications
4
60
1
Order By: Relevance
“…Actually, the 3H-labelled Challis and Is57 cells used in this study possessed a cell-associated GTF-activity of 2.5 and 0.0 mU per 10 s cells, respectively. Vickerman et al [29] have recently indicated that the strain Challis grown in a sucrose-supplemented FMC medium accumulates on glass surfaces, but its spontaneous GTF-negatire variant does not. Therefore, it is probable that the ceil-associated GTF activity of S. gordonii, in addition to mutans streptococcal GTF(s), participates in the sucrose-dependent celi-to-pellicle attachment of S. gordonii cells, However, whether the cell-associated activity is essential or not, and how many distinct GTFs are involved in this process, is yet unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the 3H-labelled Challis and Is57 cells used in this study possessed a cell-associated GTF-activity of 2.5 and 0.0 mU per 10 s cells, respectively. Vickerman et al [29] have recently indicated that the strain Challis grown in a sucrose-supplemented FMC medium accumulates on glass surfaces, but its spontaneous GTF-negatire variant does not. Therefore, it is probable that the ceil-associated GTF activity of S. gordonii, in addition to mutans streptococcal GTF(s), participates in the sucrose-dependent celi-to-pellicle attachment of S. gordonii cells, However, whether the cell-associated activity is essential or not, and how many distinct GTFs are involved in this process, is yet unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria may bind directly to the enzyme and its glucan products (8,14,33) or may bind to amphipathic molecules such as lipoteichoic acids that are complexed to glucans (29,42). Although sucrose-associated accumulation mechanisms are best defined for mutans streptococci (24), recent evidence suggests that sucrose and resulting glucan synthesis may be important in the accumulation of 5. gordonii strain Challis (40). These in vitro studies show that accumulation may be facilitated by passive occlusion of multiplying bacterial cells, as glucans are synthesized in the developing dental plaque (41).…”
mentioning
confidence: 85%
“…Cultures were mutagenized with nitrosoguanidine (28), cultured overnight in brain heart infusion broth (Difco Laboratories, Detroit, MI) and then washed and suspended in buffered KCl (1) to a concentration of IX10^ bacteria/ml. Bacterial suspensions were then mixed (Labquake, Labindustries, Berkeley, CA) with equal volumes of 2.5% (wt/vol) hydroxyapatite fiakes (BDH, Poole, UK) that had been coated with heat-sterilized (60°C), whole, unstimulated saliva (40). After 60 min of mixing, the fiakes were allowed to settle out by gravity, and the bacteria that remained unattached in the supernatants were cultured and subjected to additional rounds of selection with saliva-coated hydroxyapatite fiakes.…”
Section: Bacteria and Mutant Strain Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase variation is thought to provide bacteria with ecologically advantageous alternatives (20), which could be particularly important in the rapid, extreme changes of the oral environment. Although the in vivo role of glucosyltransferase phase variation is unknown, in vitro studies with S. gordonii Spp"" and Spp" strains suggest that these cells have different abilities to attach to and accumulate on various surfaces under different environmental conditions (30)(31)(32) and provide intriguing preliminary evidence that glucosyltransferase phase variation may allow differential colonization of oral sites. Additional phenotypic changes in cell surface properties that potentially could affect colonization, such as the ability of the cells to coaggregate or produce hemolysin, also undergo reversible phase variation in S. gordonii (11).…”
mentioning
confidence: 99%